Electromechanical performance of poly(vinylidene fluoride)/carbon nanotube composites for strain sensor applications - Ferreira, A. (2012)
This paper reports on the piezoresistive behavior of polymer based nanocomposites, composed of poly(vinylidene fluoride) – PVDF and carbon nanotubes (CNTs). The samples were prepared by hot pressing with CNT sample concentrations up to loadings of 10 wt.%. The phase present in the polymer was the -phase. The correlation between the electrical resistivity and mechanical solicitations is presented in this work for the different composites and for varying mechanical solicitations. The values of the gauge factor, ranging up to 6.2, and the linearity of the response over a wide strain range shows the viability of these materials to be used as piezoresistive sensors. The stability of the signal, the time response and the temperature behavior were also evaluated. The observed electrical and electromechanical behavior can be explained in the framework of the percolation theory.